(untitled) (Fountain Journal of Natural and Applied Sciences, 2020)
Cochlospermum planchonii is used for treatment of cardiovascular diseases in Nigeria and in some other African countries. This study investigated the anti-hyperlipidemic activity of polyphenol-rich extract of C. planchonii root in triton X-induced hyperlipidemic rats. Polyphenols were extracted from roots of C. planchonii with 80% aqueous methanol and acetone. Thirty female albino rats were randomized into six groups of five (5) rats each, Group I the non-hyperlipidemic control received saline only, group II the hyperlipidemic group received only saline, group III served as hyperlipidemic rats treated with 10 mg/kg b.w. atorvastatin while group(s) V-VII were hyperlipidemic rats treated with 25, 50 and 100 mg/kg b.w polyphenol-rich extract of C. Planchonii respectively. The effect of the administration of the extract on the serum lipid profile and hematological parameters was investigated. C. planchonii roots contained 47.7 ± 0.23 mg gallic acid equivalent / g dry extract and 49.14 ± 0.23 mg quercetin acid equivalent / g dry extract. Significant (p < 0.05) increase observed in serum total cholesterol, triacylglycerol and low-density lipoprotein with concomitant reduction in high-density lipoprotein concentration were mitigated by the polyphenol-rich extract. No significant changes were observed in the hematological indices of the hyperlipidemic rats at the doses investigated when compared to the control. The results indicated that polyphenol-rich extract of C. planchonii root exhibited anti-hyperlipidemic activity. Thus, it could be promoted as a recipe for protection against hyperlipidemia. Keywords: hyperlipidemia, Cochlospermum planchonii, polyphenol, lipid profile